PENCATATAN SAHAM LEWAT BELAKANG (BACKDOOR LISTING) MELALUI AKUISISI TERBALIK SESUAI PSAK 22 - Sugeng Wahono; Ngadiman (Jurnal Kontemporer Akuntansi, 2024)
This research aims conducted by doing cost benefit analysis in Reverse Take Over (RTO) backdoor listingtransaction compare with normal Initial Public Offering (IPO) in a case of acquisition PT MI Tbk by PT PAC. Themethods are study of documents, interviews, observation, and based on involvement experiences in the transaction.The conclusion achieved based on research are that the benefits of RTO backdoor listing transaction are gettingPAC to have listing status with firmed, controlled and faster than IPO due to not having complex documentation inoperational, legal and accounting aspects. However, as the compensation, PAC must be higher costs, mostlybecause of purchase of shares at a premium price of Rp. 50 (fifty rupiah) considering that PT MI Tbk has a fairvalue of shares of zero rupiah, negative equity and negative working capital.